Food Demand Sensitivity During the COVID-19 Pandemic in Indonesia - Riniati, Riniati; Putri, Chamelia; Lutfhi, Agus (Journal Research of Social Science, Economics, and Management, 2022)
The COVID-19 pandemic that hit Indonesia caused a decline in agricultural production, rising food prices, restrictions on export-import activities, and a decrease in food and non-food consumption. The purpose of this study was to determine the demand for staple food during the pandemic era, to examine household budget allocations and to determine price elasticity and income elasticity. This study uses expenditure data for consumption of the Indonesian population based on the results of the March 2020 Susenas. Data analysis uses the AIDS model. The results of the analysis show that rice is the main staple food with a share of expenditure of 52% in urban areas and 57% in rural areas, followed by chicken meat, eggs, cooking oil, sugar and milk, respectively. Comparison of consumption between before and during the pandemic era shows an increase in consumption for all commodities other than milk and sugar in urban areas, while in rural areas consumption decreases for rice, milk and sugar. The share of staple food expenditure is significantly influenced by prices and income in urban areas, while in rural areas prices and incomes have no significant effect. Both in urban and rural areas, the highest income elasticity is for chicken meat and eggs, while rice, cooking oil and sugar are considered inferior goods. The pandemic era is the right moment for the government to promote local food to accelerate food diversification programs.